Developmental change in the association between adolescent depressive symptoms and the home environment: results from a longitudinal, genetically informative investigation - Hannigan, Laurie J. (J Child Psychol Psychiatry, 2017)
BACKGROUND: Depression is already highly prevalent by late adolescence, indicating that research into its developmental emergence should consider earlier risk factors and environmental contexts. The home environment is a key context for children and adolescents throughout development. However, the nature of relationships that exist between aspects of the home environment and the development of depressive symptoms cannot be assumed. Genetically informative studies have been used to provide insights about the aetiology of such relationships, often finding them to be partly confounded by the influence of children's genes. Here, we investigate developmental change in the aetiology of the association between aspects of the home environment and depressive symptoms at the onset of adolescence. METHODS: We used longitudinal child‐ and parent‐report data from >5,000 twin pairs enrolled in the UK‐representative Twins Early Development Study. Multivariate, genetically sensitive structural equation models were used to decompose latent variance and covariance in depressive symptoms (measured at 12 and 16 years) and aspects of the home environment (at 9 and 14 years) into genetic and environmental influences. RESULTS: Going from childhood to adolescence, genetic influences accounted for an increasing proportion of the association [30% (16–42) of r = .44 in childhood; 40% (25–61) of r = .43 in adolescence], at the expense of shared environmental influences, which decreased from 70% (58–83) to 48% (29–62). Unique environmental influences accounted for a significant proportion of the association in adolescence only [12% (06–18)]. Developmental changes could largely be attributed to subtle shifts in the relative importance of stable aetiological factors, rather than the emergence of influences unique to adolescence. CONCLUSIONS: These findings emphasise the importance of developmental and aetiological context in interpreting associations between aspects of the home environment and child emotional outcomes.